Autotransplantation in combination with orthodontic treatment - Racha Hariri; Emad Eddin M. Alzoubi (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Autotransplantation is a surgical method in which a tooth is repositioned within the same patient. It can be described as a controlled reimplantation of an extracted tooth into a new, surgically prepared socket. The key to success of this treatment is the preservation and regeneration of the periodontal ligament. It is an underutilized technique which, if conducted with a multidisciplinary team, can be an ideal treatment option for patients with failing or missing teeth. OBJECTIVES: The detailed clinical procedures, indications for this technique, and the factors affecting its success are discussed.